Nutritive value of sugarcane silage treated with urea and added ground corn ears - Andrade, João Batista de; Júnior, Evaldo Ferrari; Braun, Gilberto (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this work was to determine the nutritive value of the silage of sugarcane treated with 0.5% of urea plus 0, 40, 80 and 120 kg of ground corn ears/ton of chopped sugarcane conserved as silage. The experiment was developed at Instituto de Zootecnia, in Nova Odessa, SP, Brazil, according to a randomized complete blocks design, with four replications. Intake and digestibility trials were made in 10, 10 and 5 day periods, corresponding to adaptation, intake and collection periods, respectively, with female sheep. The addition of ground corn ears improved fermentation pattern of the silages. The silage nutritive value measured as dry matter and neutral detergent fiber intake, dry matter and neutral detergent fiber digestibility coefficients and total digestible nutrients intake increased linearly with levels of ground corn ears.